KNOWLEDGE, ATTITUDE, AND PRACTICE OF MOTHERS ON ACUTE RESPIRATORY INFECTION IN CHILDREN UNDER FIVE YEARS - Yolanda, Ignatia Thassya; Septiandani, Lydia Putri; Sirait , Maria Nespita; Siregar, Deborah (International Journal Multidisciplinary (IJMI), 2024)
Background: Acute Respiratory Infection (ARI) significantly affects the respiratory tract, contributing to high mortality rates and a decline in quality of life for children under five, with an incidence of 3-5 episodes per child annually. In Indonesia, ARI remains prevalent, with cases increasing in 2015 (63.45%) and reaching 48.56% in Tangerang Regency by 2017. Knowledge Gap: Despite these figures, there is limited research on maternal knowledge, attitudes, and practices concerning ARI prevention. Aims: This study aims to analyze maternal knowledge, attitudes, and actions in Binong Village regarding ARI prevention among toddlers. Methods: A cross-sectional quantitative design was employed, with 50 mothers of toddlers completing a Google Forms questionnaire. Accidental sampling was used, and univariate analysis was applied to assess frequency and percentage distributions of the variables. Results: The findings revealed that 74% of mothers exhibited poor knowledge, while 100% had positive attitudes and 84% engaged in good practices toward ARI prevention. Novelty: This study highlights the discrepancy between maternal knowledge and attitudes/practices, showing that even with poor understanding, mothers maintain positive attitudes and preventive actions. Implications: The results underscore the need for improved educational interventions targeting maternal knowledge on ARI, as current positive attitudes and practices could be enhanced with better information. Future research should explore factors influencing ARI incidence in infants to develop more comprehensive prevention strategies. Ethical approval for the study was granted (085 / KEP-FON / III-2020).acute respiratory infection,